2023
DOI: 10.5296/ire.v11i2.21012
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Leadership Styles on Teacher Job Satisfaction in Nigerian Secondary Schools

Angwaomaodoko, Ejuchegahi Anthony

Abstract: In an educational environment, school administration and leadership is regarded as one of the essential components for effective institutions, in addition to instruction and learning. The research set out to investigate the impact of school managers' and leaders' leadership philosophies on teachers' work satisfaction. The goal of the research is to identify the prevalent leadership style as viewed by teachers, to gauge teachers' job satisfaction, and to investigate the connection between teachers' job satisfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…However, the context of job satisfaction for physical education teachers has not addressed certain variables. For example, research has shown that effective leadership in the school environment has a significant influence on teacher job satisfaction (Angwaomaodoko, 2023;Hashim et al, 2023;Mohammad, 2023). In addition, school climate also plays a major role in improving teacher job satisfaction, as revealed by research by (Zholchieva et al, 2023).…”
Section: Rq3 What Are the Variables That Contribute To Physical Educa...mentioning
confidence: 99%
“…However, the context of job satisfaction for physical education teachers has not addressed certain variables. For example, research has shown that effective leadership in the school environment has a significant influence on teacher job satisfaction (Angwaomaodoko, 2023;Hashim et al, 2023;Mohammad, 2023). In addition, school climate also plays a major role in improving teacher job satisfaction, as revealed by research by (Zholchieva et al, 2023).…”
Section: Rq3 What Are the Variables That Contribute To Physical Educa...mentioning
confidence: 99%